ADAPTATION OF SOUTH CAUCASIAN IMMIGRANTS IN MODERN-DAY SWITZERLAND - BABICH, Irina (CENTRAL ASIA AND THE CAUCASUS, 2021)
The article examines the main aspects of the adjustment of political and work immigrants from the South Caucasus (Georgia, Armenia, Azerbaijan) who settled in Switzerland in the 1990s and 2000s. Field ethnographic materials were collected in 2018-2019. In the course of the study, the peculiarities of the perception of the culture, lifestyle, and the value system of the Swiss were analyzed. Separately, the author examined the types of immigrants’ employment in the new country. The article’s main focus is the age factor in the adjustment and integration processes. The study also addresses the problems of the preservation of Caucasian cultures and languages under the conditions of immigration and the formation of communication environments for South Caucasians in Switzerland. The author concludes that the South Caucasian immigrants are united by professional and social criteria rather than ethnic kinship. The adults adapt to the new conditions, and the youth integrates and acquires a Swiss identity. Elements of Caucasian cultures, languages and environment are gradually being lost in Switzer- land.